RESEARCH OF THE FEATURES OF DIGITAL SIGNAL FORMATION IN SATELLITE COMMUNICATION LINES - Мagro V. І.; Panfilov, O. G. (Radio Electronics, Computer Science, Control, 2024)
Context. Remote sensing of the Earth is now widely used in various fields. One of the challenges of remote sensing is the creation of inexpensive satellite systems operating in polar circular orbits. These systems require the development of a receptiontransmission system that allows tens of gigabits of video information to be transmitted to an earth receiving station within ten minutes. That is, there is a need to create a communication system that provides high speed data transmission from small satellites weighing up to 50 kg. Objective. The aim of the work is to study the features of digital signal formation in modern satellite communication lines and to develop a communication system with a high data transfer rate (usually 300 Mbit/s), which can be applied to small Earth Observation satellites. Method. Proposed concept for building a high-speed data transmitter from a remote sensing earth satellite using commercially available off-the-shelf technology. Calculations of the power flow density created at the input of the receiving earth station were performed to find out the possible power of the on-board transmitter. Results. A diagram of a communication system based on the DVB-S standard using the technology of commercially available off-the-shelf products has been developed. The high-speed data transmitter is implemented on a Xilinx® Zynq Ultrascale+ ™ MPSoC FPGA microchip, which is located on an Enclustra Mercury XU8 module with a high-performance dual 16-bit AD9174 DAC. The on-board transmitter with a power of up to 2 W meets the requirements of the ITU Radio Regulations for the power flux density on the surface of the Earth, which is created by the radiation of the space station EESS in the range 8025–8400 MHz. It is shown that the energy reserve of the communication line of 3 dB is achieved for various commands for coding and modulation changes with an increase in the elevation angle, which allows to increase the speed of information transmission. Conclusions. An original receiving-transmitting system was developed for use in small satellites for remote sensing of the Earth. It is shown that the function of adaptive modeling of ACM of the DVB-S standard allows you to automatically change the transmission parameters in real time depending on the changing conditions of the channel, providing opportunities for more flexible and effective data transmission in various conditions, which will allow to increase the volumes of information transmitted by communication session. The proposed system operates in the X-band and is built using commercially available off-the-shelf products. An antenna with double circular polarization is used as the emitter. Two physical channels represent two polarization modes: right circular polarization and left circular polarization, each of which has three frequency channels.